Initial pH of medium affects organic acids production but do not affect phosphate solubilization - Marra,Leandro M. (2015)
The pH of the culture medium directly influences the growth of microorganisms and the chemical processes that they perform. The aim of this study was to assess the influence of the initial pH of the culture medium on the production of 11 low-molecular-weight organic acids and on the solubilization of calcium phosphate by bacteria in growth medium (NBRIP). The following strains isolated from cowpea nodules were studied: UFLA03-08 (Rhizobium tropici), UFLA03-09 (Acinetobacter sp.), UFLA03-10 (Paenibacillus kribbensis), UFLA03-106 (Paenibacillus kribbensis) and UFLA03-116 (Paenibacillus sp.). The strains UFLA03-08, UFLA03-09, UFLA03-10 and UFLA03-106 solubilized Ca3(PO4)2 in liquid medium regardless of the initial pH, although without a significant difference between the treatments. The production of organic acids by these strains was assessed for all of the initial pH values investigated, and differences between the treatments were observed. Strains UFLA03-09 and UFLA03-10 produced the same acids at different initial pH values in the culture medium. There was no correlation between phosphorus solubilized from Ca3(PO4)2 in NBRIP liquid medium and the concentration of total organic acids at the different initial pH values. Therefore, the initial pH of the culture medium influences the production of organic acids by the strains UFLA03-08, UFLA03-09, UFLA03-10 and UFLA03-106 but it does not affect calcium phosphate solubilization.